The Microtubule-Associated Protein Tau and Its Relevance for Pancreatic Beta Cells - Magdalena Maj; Gregor Hoermann; Sazan Rasul; Wolfgang Base; Ludwig Wagner; Johannes Attems (Journal of Diabetes Research)
Structural and biochemical alterations of the microtubule-associated protein tau (MAPT) are associated with degenerative disorders referred to as tauopathies. We have previously shown that MAPT is present in human islets of Langerhans, human insulinomas, and pancreatic beta-cell line models, with biophysical similarities to the pathological MAPT in the brain. Here, we further studied MAPT in pancreatic endocrine tissue to better understand the mechanisms that lead to functional dysregulation of pancreatic beta cells. We found upregulation of MAPT protein expression in human insulinomas when compared to human pancreatic islets of Langerhans and an imbalance between MAPT isoforms in insulinomas tissue. We cloned one 3-repeat domain MAPT and transduced this into a beta-cell derived rodent cell line Rin-5F. Proliferation experiments showed higher growth rates and metabolic activities of cells overexpressing MAPT protein. We observed that a MAPT overexpressing cell line demonstrates altered insulin transcription, translation, and insulin secretion rates. We found the relative insulin secretion rates were significantly decreased in a MAPT overexpressing cell line and these findings could be confirmed using partial MAPT knock-down cell lines. Our findings support that MAPT may play an important role in insulin granule trafficking and indicate the importance of balanced MAPT phosphorylation and dephosphorylation for adequate insulin release.